Cultivating Loving Kindness: A Two-Stage Model of the Effects of Meditation on Empathy, Compassion, and Altruism - Kristeller, Jean L. (Zygon, 2005)
Abstract. We explore the role of meditative practice in cultivating experiences of compassion, empathy, and altruism and address an apparent paradox: Meditation often is associated with solitary retreat, if not preoccupation with one's own concerns. How, then, does such a practice promote compassion for others? We propose a two-stage model. The first stage involves disengagement from usual preoccupation with self-reinforcing, self-defeating, or self-indulgent behaviors and reactions; the second involves a focused engagement with a universal human capacity for altruistic experience, love, and compassion. Reference is made to the limited research literature and to clinical applications of loving kindness (metta) meditation in cultivating these processes.